Investigation of an isolated case of human Crimean–Congo hemorrhagic fever in Central Uganda, 2015. (March 2018) - Balinandi, Stephen; Patel, Ketan; Ojwang, Joseph; Kyondo, Jackson; Mulei, Sophia; Tumusiime, Alex; Lubwama, Bernard; Nyakarahuka, Luke; Klena, John D.; Lutwama, Julius; Strӧher, Ute; Nichol, Stuart T.; et al.
Highlights: Laboratory confirmation of a single human CCHF case in Kakaseke District, Uganda. Genomic sequencing of viral isolate shows it falls in the DRC (Africa 2) lineage. Investigations showed only a single tick had evidence of CCHFV RNA by RT-PCR. This outbreak highlights the importance of VHF surveillance for early detection. Abstract: Background: Crimean–Congo hemorrhagic fever (CCHF) is the most geographically widespread tick-borne viral infection. Outbreaks of CCHF in sub-Saharan Africa are largely undetected and thus under-reported. On November 9, 2015, the National Viral Hemorrhagic Fever Laboratory at the Uganda Virus Research Institute received an alert for a suspect VHF case in a 33-year-old male who presented with VHF compatible signs and symptoms at Mengo Hospital in Kampala. Methods: A blood sample from the suspect patient was tested by RT-PCR for CCHF and found positive. Serological testing on sequential blood specimens collected from this patient showed increasing anti-CCHFV IgM antibody titers, confirming recent infection. Repeat sampling of the confirmed case post recovery showed high titers for anti-CCHFV-specific IgG. An epidemiological outbreak investigation was initiated following the initial RT-PCR positive detection to identify any additional suspect cases. Results: Only a single acute case of CCHF was detected from this outbreak. No additional acute CCHF cases were identified following field investigations. Environmental investigations collected 53 tick samples, with only 1, a Boophilus decoloratus, having detectable CCHFV RNA by RT-PCR. Full-length genomic sequencing on a viral isolate from the index human case showed the virus to be related to the DRC (Africa 2) lineage. Conclusions: This is the fourth confirmed CCHF outbreak in Uganda within 2 years after more than 50 years of no reported human CCHF cases in this country. Our investigations reaffirm the endemicity of CCHFV in Uganda, and show that exposure to ticks poses a significant risk for human infection. These findings also reflect the importance of having an established national VHF surveillance system and diagnostic capacity in a developing country like Uganda, in order to identify the first cases of VHF outbreaks and rapidly respond to reduce secondary cases. Additional efforts should focus on implementing effective tick control methods and investigating the circulation of CCHFV throughout the country.